Host hybridization as a potential mechanism of lateral symbiont transfer in deep‐sea vesicomyid clams. Issue 21 (23rd September 2019) - Breusing, Corinna; Johnson, Shannon B.; Vrijenhoek, Robert C.; Young, Curtis R.
Abstract: Deep‐sea vesicomyid clams live in mutualistic symbiosis with chemosynthetic bacteria that are inherited through the maternal germ line. On evolutionary timescales, strictly vertical transmission should lead to cospeciation of host mitochondrial and symbiont lineages; nonetheless, examples of incongruent phylogenies have been reported, suggesting that symbionts are occasionally horizontally transmitted between host species. The current paradigm for vesicomyid clams holds that direct transfers cause host shifts or mixtures of symbionts. An alternative hypothesis suggests that hybridization between host species might explain symbiont transfers. Two clam species, Archivesica gigas and Phreagena soyoae, frequently co‐occur at deep‐sea hydrocarbon seeps in the eastern Pacific Ocean. Although the two species typically host gammaproteobacterial symbiont lineages marked by divergent 16S rRNA phylotypes, we identified a number of clams with the A. gigas mitotype that hosted symbionts with the P. soyoae phylotype. Demographic inference models based on genome‐wide SNP data and three Sanger sequenced gene markers provided evidence that A. gigas and P. soyoae hybridized in the past, supporting the hypothesis that hybridization might be a viable mechanism of interspecific symbiont transfer. These findings provide new perspectives on the evolution of vertically transmitted symbionts and their hosts in deep‐sea chemosynthetic environments. Abstract : see also the Perspective by Wilkins